Effect coffee administration on alkaline phosphatase levels during relapse following orthodontic retention in rats: an experimental study - Tyas, Septa Yumnaning; Abdurrohman, Muhamat Muhtar S; Mahardika, Christina; Yusuf, Moh (Padjadjaran Journal of Dentistry, 2024)
Introduction: Maintaining teeth in their corrected positions following orthodontic treatment can be extremely challenging. Coffee is one substance whose effects on relapse have been extensively studied. The aim of study is to analyze the effect of coffee administration on relapse after orthodontic retention by evaluating alkaline phosphatase levels. Methods: This experimental laboratory study enrolled SpraqueDawley rats, with brackets applied using Edgewise slot 0.022” system and a nickel-titanium open coil spring fixed between the lower central incisors for 14 days. Based on Federer’s formula, 36 SpraqueDawley rats were randomly divided by simple random sampling into four groups: Group 1 (no retention), Group 2(retention for 3 days), Group 3(retention for 7 days), and Group 4(retention for 2 weeks). The Spraque-Dawley rats in the four experimental groups were given aquadest, 50 mg, and 100 mg/kg coffee intake ad libitum. Orthodontic relapse was assessed by measuring changes in alkaline phosphatase levels between the lower central incisors (the relapse side). Changes in the distance between the central incisors during relapse were observed visually. Alkaline phosphatase levels, which serve as a predictor of recurrence, were determined using an enzyme-linked immunosorbent assay (ELISA). Data analysis was conducted with the Two-way analysis of variance (ANOVA) and a post hoc Tukey test. Results: Overall, we found that a longer retention period was associated with a slower rate of relapse and a shorter overall amount of relapse. In addition, inhibiting osteoclast formation using coffee also reduced orthodontic relapse. Alkaline phosphatase (ALP) and/or its biomarkers could serve as potential therapeutic targets in the prevention and treatment of orthodontic relapse, with changes observed at a value of 0.001. This demonstrates that coffee administration affects alkaline phosphatase levels during relapse after orthodontic retention. Conclusion: Coffee administration increased alkaline phosphatase levels during relapse after orthodontic retention in rats.